PENGELOLAAN PENINGKATAN MUTU MADRASAH - Erlina Farida (Jurnal Dialog, 2014)
An excellent madrassa is obviously reflected by its quality. This quality is possessed by MTs Mu’allimaat Yogyakarta which has managed to become one of the favorite and superior madrassas. This is due to the integrity of its human resources that are supported by adequate infrastructures. Another supporting components for the excellence of the madrassa is the wide networks and strong supports of the community members, organizations, and the government. Professionalism and managerial independence also contribute to the success of this madrassa, proven by the academic and non academic achievements of its students. This paper investigates the management of quality improvement in MTs Muallimaat Yogyakarta.